Desain Pembelajaran Berdiferensiasi Pada Materi Aritmatika Sosial Siswa Kelas VII SMPK Giovanni Kupang - Djegho, Edith Stein Bara (Fraktal : Jurnal Matematika dan Pendidikan Matematika, 2025)
The main reason of this study was the condition of some students who could not do the learning instruction and usually accepted the learning material slowly, so made them missed the process and even needed more time than usual. One of the reasons was the learning instruction which never gave more attentions for the student’s needs and conditions. Because of that, this study aimed to produce the desain of differentiated instruction learning on social arithmetic material, especially at seventh degree students of SMPK Giovanni Kupang. The kind of this study was desain research. This study done at SMPK Giovanni Kupang with the subject was the group of seventh degree students. The technique of data collecting in this study consisted of test, observation, and interview. This study used the descriptive-qualitative and quantitaive as the technique of data analysis. Qualitative datas was gained by the result of interview activities and observation, meanwhile qualitative datas was gained by the result of assesment. This study produced the desain of differentiated instruction learning that focussed at content learning and could used to support social arithmetic material. The results showed that mathematic learning by using the desain of differentiated learning in content could used effectively because the student could knew and understood the learning material well while increased their learning outcome.